PIPERACILLIN-TAZOBACTAM AS A COST EFFECTIVE MONOTHERAPY IN FEBRILE NEUTROPENIA - Fasih, Samir; Siddiqui, Neelam; Muza, Narjis; Hannan, Abdul; Sarwar, Sohail; Shafi, Azhar; Athar, Sohail (Journal of Ayub Medical College Abbottabad, 2013)
Background: Fever in neutropenic patient is a medical emergency. Timely intervention with antibiotics has been demonstrated to be effective. We assessed Piperacillin-Tazobactem as a cost effective mono-therapy in solid malignancy patients in our institution in relation to dual antibiotic therapy and other monotherapies. Methods: This study was conducted to determine the efficacy, and cost effectiveness of Piperacillin-Tazobactem as monotherapy in febrile neutropenia. Total 150 patients with chemotherapy induced febrile neutropenia were selected. Piperacillin-Tazobactem was given intravenously 4500 mg every 6 hour. Outcome was assessed as success and failure. Success was defined as afebrile for four consecutive days, clearance of signs of infection, no new cultures, and no recurrence of primary infection after completion of therapy. Failure was defined as modification or addition of antibiotic due to clinical deterioration, cultured organism resistant to Piperacillin-Tazobactem and Death. Results: The mean age was 43 years, 31% males and 69% were females. Out of total 150 patients, 73 patients were of breast carcinoma. There were 143 patients with negative blood cultures, and 7 patients with positive blood cultures, out of which 3 patients were resistant to Piperacillin-Tazobactem. Success was achieved in 83.3% of total patients. Daily cost of Piperacillin-Tazobactem was much less in relation to other monotherapies and dual antibiotic therapy including Gentamicin. None of the patient had adverse effects of Piperacillin-Tazobactem. Conclusion: We concluded that Piperacillin-Tazobactem is a safe, well tolerated as well as cost effective monotherapy in patient with febrile neutropenia with solid cancers. Only two percent organisms were resistant to Pipercillin-Tazobactam. Keywords: Febrile Neutropenia, Pipercacillin-Tazobactem, Monotherapy